2015
DOI: 10.1038/mt.2014.197
|View full text |Cite
|
Sign up to set email alerts
|

miR-382 Inhibits Osteosarcoma Metastasis and Relapse by Targeting Y Box-Binding Protein 1

Abstract: Lung metastasis and relapse in osteosarcoma (OS) patients indicate poor prognosis. Here, we identified significantly decreased expression of miR-382 in highly metastatic OS cell lines and relapsed OS samples compared to their parental cell lines and primary OS samples, respectively. In addition, our clinical data showed that the miR-382 expression level was inversely associated with relapse and positively associated with metastasis-free survival in OS patients. The overexpression of miR-382 suppressed epitheli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 88 publications
(98 citation statements)
references
References 50 publications
3
94
1
Order By: Relevance
“…The inhibition of miR-382 upregulated E-cadherin expression and altered the cellular phenotypes in diabetic kidneys [26, 29]. In cancer, miR-382 was shown to suppress osteosarcoma metastasis by targeting YB-1 oncogene [30, 31]. The regulatory roles of hsa-miR-382-5p in tendon biology remain unexplored and in our study, downregulation of hsa-miR-382-5p and was found to hold a strong correlation with increased ECM damage in Group 1 tendons suggesting its role in maintaining tendon ECM integrity.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of miR-382 upregulated E-cadherin expression and altered the cellular phenotypes in diabetic kidneys [26, 29]. In cancer, miR-382 was shown to suppress osteosarcoma metastasis by targeting YB-1 oncogene [30, 31]. The regulatory roles of hsa-miR-382-5p in tendon biology remain unexplored and in our study, downregulation of hsa-miR-382-5p and was found to hold a strong correlation with increased ECM damage in Group 1 tendons suggesting its role in maintaining tendon ECM integrity.…”
Section: Discussionmentioning
confidence: 99%
“…The lower wells contained the same medium supplemented with 10% serum. After 24 hr, the cells that had migrated to the lower side of the chamber were fixed, dyed, and counted as previously described 14 . For the osteosphere formation assay, 1,000 cells were seeded in six-well ultra-low cluster plates (Corning) and cultured for 8 days.…”
Section: Methodsmentioning
confidence: 99%
“…MicroRNA-133a is demonstrated to be decreased in OS and acts as a tumor suppressor by targeting Bcl-xL and Mcl-1 [11]. Downregulation of miR-382 encourages OS metastasis and relapse by targeting Y Boxbinding protein 1 [12]. The miR-183 expression is remarkably associated with OS metastasis by regulating Ezrin [13].…”
Section: Introductionmentioning
confidence: 96%